1995
DOI: 10.1111/j.1095-8649.1995.tb01927.x
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation trials of juvenile Italian sturgeon to different salinities: morpho‐physiological descriptors

Abstract: In this study the first experimental trials of acclimation to salinities of the Italian sturgeon Acipenser naccarii are described. Preliminary observations regarding some morphological features of the gut, kidney and gills following exposure to 20 and 30‰ salinity are reported, and compared with those displayed by many teleosts in hyper-and hypoosmoregulation. Results are discussed with regard to the osmoregulatory mechanisms and to the physiological limits of adaptability of this species in the second year of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
34
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 21 publications
(10 reference statements)
13
34
0
Order By: Relevance
“…In some other studies also, the gill NKA activity followed this pattern, as the lowest NKA activity levels were obtained in brackishwater conditions (Laiz-Carrion et al, 2005;Kang et al, 2008;Kang et al, 2012;Khodabandeh et al, 2009a). Since NKA is highly expressed in fish gill ionocytes, its activity at the gill level is expected to be reduced with decreased ionocyte size and number (Evans, 1993;Cataldi et al, 1995;McCormick, 1996;McKenzie et al, 1999;Mancera and McCormick, 2000). Low values of the ionocyte size, number and the gill NKA activity reported previously in the literature for fish acclimated to brackishwater has been confirmed in the current study, especially for 1g fingerlings, by a reduction in the number and size of ionocytes under similar conditions.…”
Section: Resultssupporting
confidence: 86%
“…In some other studies also, the gill NKA activity followed this pattern, as the lowest NKA activity levels were obtained in brackishwater conditions (Laiz-Carrion et al, 2005;Kang et al, 2008;Kang et al, 2012;Khodabandeh et al, 2009a). Since NKA is highly expressed in fish gill ionocytes, its activity at the gill level is expected to be reduced with decreased ionocyte size and number (Evans, 1993;Cataldi et al, 1995;McCormick, 1996;McKenzie et al, 1999;Mancera and McCormick, 2000). Low values of the ionocyte size, number and the gill NKA activity reported previously in the literature for fish acclimated to brackishwater has been confirmed in the current study, especially for 1g fingerlings, by a reduction in the number and size of ionocytes under similar conditions.…”
Section: Resultssupporting
confidence: 86%
“…In marine/estuarine teleosts of different origin (Myoxocephalus octodecemspinosus, Acipenser naccarii, P. orbignyanus, S. testudineus, and S. greeleyi), plasma ion concentration is kept within narrow limits in diluted seawater or even in freshwater, indicating euryhalinity and a welldeveloped capacity of osmoionic regulation (Claiborne et al, 1994;Cataldi et al, 1995;Prodócimo & Freire, 2001;Sampaio & Bianchini, 2002), as found in our study.…”
Section: Discussionsupporting
confidence: 79%
“…A Normal structure (ne) of gills and branchial epithelial lifting (el); B gills aneurisms (arrows); C normal liver structure; D melanomacrophage center (mm); E vacuolization of liver tissue and melanomacrophage centers (mm); F, Hemorrhagic area (ha); G area of necrosis (na) et al 2002). These plasma alterations reflect pollutants responses, as estuarine fishes are excellent osmoregulators (Plaza-Yglesias et al 1988;Cataldi et al 1995, Plaut 1998, Prodocimo and Freire 2001Freire and Prodocimo 2007), even when exposed to a wide range of salinities; the salinity difference between both sites was negligible. Osmoregulatory blood parameters are indeed considered useful biomarkers of pollution in estuarine environments, also when coupled to the analysis of impairment of the activity of key enzymes from the osmoregulatory organs, such as the Na + , K + -ATPase or the carbonic anhydrase (reviewed in Monserrat et al 2007).…”
Section: Discussionmentioning
confidence: 99%